All‐in‐One Sensing System for Online Vibration Monitoring via IR Wireless Communication as Driven by High‐Power TENG. Issue 16 (9th March 2023) - Wu, Han; Wang, Zihan; Zhu, Boyu; Wang, Hanqing; Lu, Chengyue; Kang, Meicun; Kang, Shenglin; Ding, Wenbo; Yang, Lijun; Liao, Ruijin; Wang, Jiyu; Wang, Zhong Lin
Abstract: Abnormal vibration is a direct response to the mechanical defects of electrical equipment, and requires reliable vibration sensing for health condition evaluation in the associated system. The triboelectric nanogenerator (TENG) triggered by random vibration to generate electrical energy/signal while giving feedback on the vibration state, paving a promising way towards self‐powered sensors. Here, an all‐in‐one sensing system configured with a vibration sensor demonstrates instantaneous discharge boosted TENG and IR wireless communication for vibration state online monitoring. The sandwich‐structured TENG combined with mechanical switches can release the co‐accumulated charges from dual triboelectric layers to yield giant instantaneous output power of 616 W, which is 10 6 times higher than that of the continuous discharge. Moreover, an IR LED as a transmitter driven by the TENG can form an all‐in‐one vibration sensor enabling wireless communication, where the sensor can be further integrated with repeaters and phones to establish a wireless vibration online monitoring system for vibration state visualization. This work presents a novel idea to implement high‐power TENG with IR communication integration for in situ vibration online monitoring. Such a strategy is potentially available for distributed sensor construction towards abnormal signal monitoring that reflects the operating state of equipment. Abstract : An all‐in‐one vibration sensor is proposed with instantaneous discharge‐boosted triboelectric nanogenerator (TENG) and IR communication. The sandwich‐structured TENG combined with mechanical switches enables co‐accumulated charges to be released simultaneously. An IR light‐emitting diode connected to a TENG is used in the construction of an all‐in‐one wireless, self powered vibration sensor. The novel concept could be potentially utilized in a power grid that delivers vibration feedback on electrical equipment.